1965
DOI: 10.1080/17470216508416422
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Temporal Changes in Free Recall

Abstract: An experimental study of short-term memory for lists of familiar English words is reported. Lists of 10, 20, and 30 unrelated words were presented at a 1-sec. rate. Retention was measured by free recall after intervals of 0, 15 and 30 sec. A counting task was used to prevent rehearsal during the retention interval. The absolute level of recall increased with length of list whereas the percentages retained showed the reverse trend. The recall scores decreased steadily as a function of retention interval, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
279
2
1

Year Published

1972
1972
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(304 citation statements)
references
References 12 publications
22
279
2
1
Order By: Relevance
“…4C), we performed an analysis of the neural correlates of the primacy effect in our data. It has been well established that rehearsal is associated with enhanced recall for early list items [i.e., the primacy effect (36)(37)(38)(39)(40)]. Thus, if our basic findings were driven by rehearsal, one might expect that participants exhibiting strong neural contiguity should also show a strong primacy effect.…”
Section: Discussionmentioning
confidence: 82%
“…4C), we performed an analysis of the neural correlates of the primacy effect in our data. It has been well established that rehearsal is associated with enhanced recall for early list items [i.e., the primacy effect (36)(37)(38)(39)(40)]. Thus, if our basic findings were driven by rehearsal, one might expect that participants exhibiting strong neural contiguity should also show a strong primacy effect.…”
Section: Discussionmentioning
confidence: 82%
“…For example, when rehearsal of initial list items is reduced or prevented by presenting a free recalllist in an incidental learning situation (Marshall & Werder, 1972) or by manipulating rehearsal strategies by instructions (Fischler, Rundus, & Atkinson, 1970;Glanzer & Meinzer, 1967;Palmer & Ornstein, 1971), the primacy effect in immediate recall is reduced or eliminated, while the recency effect continues to be present. On the other hand, if rehearsal of terminal input positions is hampered by introducing a filled delay interval before the immediate test, the recency effect is reduced, while primacy continues to be manifested (Glanzer & Cunitz, 1966;Postman & Phillips, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…An important problem for this research is that many studies have failed to find a negative recency effect in an initial recall test delayed by an irrelevant interpolated activity (e.g., Bruce & Crowley, 1970;Glanzer & Cunitz, 1966;Glanzer, Gianutsos, & Dubin, 1969;Jacoby & Bartz, 1972;Postman & Phillips, 1965;Raymond, 1969;Richardson & Baddeley, 1975). Watkins and Watkins (1974) suggested that an irrelevant distractor task induced an elaborative mode of rehearsal for the last few list items.…”
Section: Variations In the Negative Recency Effect John T E Richardmentioning
confidence: 99%